2013
DOI: 10.9781/ijimai.2013.216
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Education through eLearning technology in Spain

Abstract: 46-Abstract -eLearning kind of education is stirring up all the disciplines in the academic circles, especially since it provides an access to educational areas that are uneasy and traditionally inperson, such as Engineering. Even though it had an outbreak in some of the most prestigious American universities, eLearning has being a reality in Spain for some years now, changing educational and teaching habits. To ensure a proper education is not an easy task with it comes to engineering fields, therefore this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In this process, the delivery of the course exercises, its correction and the feedback generated is performed by the system automatically. Rodríguez et al (2013) proposed that the Artificial Intelligence techniques were integrated into the e-learning platform of the engineering laboratory practices (System and Automation Engineering Laboratories) to form a teacher-cognitive system combination.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, the delivery of the course exercises, its correction and the feedback generated is performed by the system automatically. Rodríguez et al (2013) proposed that the Artificial Intelligence techniques were integrated into the e-learning platform of the engineering laboratory practices (System and Automation Engineering Laboratories) to form a teacher-cognitive system combination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In engineering education, previous studies generally found a positive relationship between traditional learning and e-learning (Rodríguez et al, 2013;Soler, 2010;Soler et al, 2006;Ubell, 2000). Previous developments on e-learning have involved computer-based assessment platforms for teaching and learning, Artificial Intelligence applications and autocorrect functions in e-learning platforms (Rodríguez et al, 2013;Soler, 2010;Soler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Form childhood on every student counts on the possibility of getting every imaginable document at a few clicks of distance. Mobile or navigational agents are the perfect tool for facilitating the students the task of search and retrieving of knowledge in any form [11]. We should make our agents more copyright-violation conscious than our students likely will be.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, e-learning method may be seen as less effective than traditional methods of learning, as it has a negative impact on the development of communication skills of the learners. Researchers have claimed that elearning is more suitable in social science and humanities than the fields such as medical Effect of attendance on student performance science and engineering where there is the need to develop practical skills (Peterson and Feisel, 2002;Fernandez-Rodriguez et al, 2013). Thus, not all educational disciplines can effectively implement e-learning in their curriculum, e.g.…”
Section: Pros and Cons Of E-learningmentioning
confidence: 99%